Perceptions of Parents and Educaators on Risky Play: Balancing Developmental Benefits and Safety in Early Childhood Education - jazariyah, jazariyah; Purnamasari, Yayu Mega; Pramesti, Intan Ayu; Supriani, Endang; Khaerunnisa, Nabilla Fitria; Vitaloka, Dea; Arifah, Rike Aulia; Sari, Nizma Dwi Kharisma (PIAUD Universitas Islam Negeri Sunan Kudus, 2024)
Risky play presents a paradox in early childhood education (ECE): while it offers significant benefits for children’s growth and development, it raises concerns among parents and teachers. This study aims to explore the perceptions of parents and educators regarding risky play in early childhood. A survey approach was employed using a mixed-methods concurrent embedded design, combining quantitative and qualitative descriptive analyses. The study involved 112 participants, comprising early childhood education teachers and parents in Java. Data were collected through questionnaires and interviews to gather insights into parental knowledge about risky play, the types of risky play, their concerns, and their expectations. Quantitative findings revealed that 77% of parents are familiar with risky play, while 30% are not. Parents expressed the highest concern for water-related activities (90.9%), followed by sliding activities (88.4%). Injuries were identified as a significant concern, with 56.6% worried about physical harm and 14.8% about peer influence. Additionally, parents and teachers highlighted the importance of receiving information on risk management in risky play. The findings of this study can inform the development of risk management programs tailored for early childhood education, ensuring a balance between developmental benefits and safety considerations